Evaluation of electrical resistivity in a tropical sandy soil compacted - Peixoto, Anna Silvia Palcheco [UNESP]; Yamasaki, Marcia Tiemi; Lodi, Paulo César [UNESP] (My University, 2014)
The utilization of electrical resistivity is a technique that leads to improve the sampling of environmental works. The bulk resistivity considers the three phases of soil mechanics theory and their intervening factors such as porosity, saturationdegree, moisture content and temperature. The current study evaluated the electrical resistivity of a compacted tropical soil (sedimentary sand), varying the salinity concentration in the percolation fluid. The tests results showed the resistivity values tend to be constant in the wet density curve of compaction test and when the degree of saturation is above 80%. It was also noted that the resistivity-suction curve has the same behavior. Considering the importance of the analyses of unsaturated soils has to tropical environmental and the time spent in the soil-water retention curve, the use of resistivity could become a technique to evaluate studies with unsaturated soils. Thus, a new electrical resistivity equation was done for both the moisture content as for the soil suction measurement. © 2014, EJGE.
Keywords: Compaction; Permeability; Salinity fluid; Soil electrical resistivity; Unsaturated soil